2022
DOI: 10.1055/s-0042-1743101
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Parameters to Predict the Severity of Hyperemesis Gravidarum and Ketonuria

Abstract: Objective Hyperemesis gravidarum (HG) is a pregnancy complication that can progress with persistent nausea and vomiting. The aim of the present study is to evaluate the relationship between hematological parameters and HG. Method A total of 532 pregnant women with HG who were admitted to the Department of Obstetrics and Gynecology between March 2019 and February 2021, and 534 healthy pregnant women with characteristics similar to those of the case group were included in the study. The hematological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…18 Another study defined the mean corpuscular hemoglobin (MCH), NLR, and PLR levels as independent predictors of the presence of HG and level of ketone positivity. 19 Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG. 20 In our study, NLR, PLR, and PCT counts were found to be significantly higher in the HG group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study defined the mean corpuscular hemoglobin (MCH), NLR, and PLR levels as independent predictors of the presence of HG and level of ketone positivity. 19 Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG. 20 In our study, NLR, PLR, and PCT counts were found to be significantly higher in the HG group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…They also stated that dehydration and the inflammatory process parallel to the severity of HG were responsible for this increase, and they suggested that PLR and PCT were important independent discriminators for HG 18 . Another study defined the mean corpuscular hemoglobin (MCH), NLR, and PLR levels as independent predictors of the presence of HG and level of ketone positivity 19 . Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The modi ed pregnancy-unique quanti cation of emesis and nausea (PUQE) index, which consists of the assessment of three components, including the duration of nausea in hours, the number of vomiting episodes, and retching within a day, was used to assess the severity of NVP [13]. The severity of nausea and/or vomiting in pregnancy is categorized using the PUQE score: mild (4-6), moderate (7)(8)(9)(10)(11)(12) and severe, also known as HG (≥ 13). The patients with moderate NVP and HG, who were almost always treated as inpatients, were de ned as patients requiring 'inpatient treatment'.…”
Section: De Nitions Characteristics Of Study Population Patient Selec...mentioning
confidence: 99%
“…The severity of nausea and/or vomiting in pregnancy is categorized using the PUQE score: mild (4-6), moderate (7)(8)(9)(10)(11)(12) and severe, also known as HG (≥ 13). The patients with moderate NVP and HG, who were almost always treated as inpatients, were de ned as patients requiring 'inpatient treatment'.…”
Section: De Nitions Characteristics Of Study Population Patient Selec...mentioning
confidence: 99%
See 1 more Smart Citation